Personality and other factors associated with smokers and non-smokers : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Albany, New Zealand - Hansen-Reid, Mette (Massey University, 2006)
The Eysenck Addiction Scale has not previously been used to measure the addictive nature of cigarette smoking. The purpose of this study was to investigate the utility of the Eysenck Addiction Scale (AS) in differentiating smokers from non-smokers, and to identify the personality factors that distinguish smokers from non-smokers. A further aim was to examine the concordance among different measures of nicotine dependence and to compare this to self-perceived nicotine dependence among cigarette smokers. A cohort of 120 first year psychology students volunteered to complete a self-report questionnaire including demographic information, smoking behaviour and the Eysenck Personality Questionnaire-Revised (EPQ-R). The Heaviness of Smoking Index and DSM-IV-TR withdrawal criteria were used to assess nicotine dependence. Non-parametric statistics were used to test differences between the personality traits, smoking behaviour, demographic characteristics and nicotine dependence measures. Daily smokers scored significantly higher on the Addiction Scale of the EPQ-R than non-smokers. Daily smokers also scored higher on the personality dimensions of Psychoticism and Extraversion; however, there were no significant differences between any of the smoking categories on Neuroticism. There were no significant correlations between the three measures of dependence. It is suggested that the measures evaluate different aspects of nicotine dependence. This finding is consistent with previous research and further highlights the need to develop a level of consistency throughout the field when assessing, treating or researching nicotine dependence. There were significant differences between smokers who considered themselves nicotine dependent and those who did not consider themselves nicotine dependent on the number of cigarettes smoked per day and their score on the addiction trait. Self perceived nicotine dependence was not correlated with the Heaviness of Smoking Index or the DSM-IV-TR Withdrawal Symptoms. This initial study suggests that the Addiction Scale is able to distinguish smokers from non-smokers on the addiction trait. It is recommended that the additional scale be calculated when the EPQ-R is administered in order to gather additional information on the personality factors associated with addiction.
Keywords: Cigarette smokers -- Psychology; Smoking -- Psychological aspects